Effects of steam explosion on yield and properties of soluble dietary fiber from wheat bran - Ma, Jianhui; Yuan, Meng; Liu, Ying; Duan, Yingxing; Zhang, Daijing; Shao, Yun; Wang, Tianlin; Jiang, Lina (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2021)
Wheat bran is abundant in dietary fiber, and an important indicator for evaluating the dietary fiber is the soluble dietary fiber (SDF) content. In this study, we analyzed the effect of steam explosion (SE) treatment on the SDF content of wheat bran. The parameters, including steam pressure, residence time, and mesh size were optimized, and it was found that the content of total SDF in wheat bran after SE treatment could be increased from 18.88% to 40.32%. The SDF characteristics from raw wheat bran and SE-treated wheat bran were investigated. The results show that the molecular weight of SDF decreased after SE treatment, and the SDF surface became disintegrated. In addition, the thermodynamic characteristic of SDF was improved after SE treatment, and similar functional groups were found to those SDF from raw wheat bran. These effects could potentially improve the physicochemical properties of SDF and increase the application value of wheat bran.